EVALUATION OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER LEARNING USING COUNTENANCE STAKE MODEL - Ziyyad Alafthoni, Fahmi (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research aims to describe the implementation of teaching of Islamic and religious education at Senior High School Jember Regency which includes planning, learning, and learning assessment, and student KKM result. It is an evaluation study using a quantitative descriptive approach with the Countenance Stake model with three phases: antecedent, transaction, outcome. The research sample comprised 9 PAI (Islamic Religious Education) teachers and 298 grade XI. The data were collected through documentation, observation, questionnaires, and interviews. The validation of the instrument was conducted through content validity and construct validity and reliability with Alpha Cronbach. The data analysis technique used the ideal criteria from Azwar. The results of this study show that: (1) The Antecedent aspects of learning planning have a 98.46% achievement with good categories. (2) The Transaction aspect includes implementing a 89.07% learning belonging to good categories and a 84.34% learning assessment with good categories. The Outcome aspect as seen from the learning outcomes of one theme has not fulfilled the Minimal submission criteria. 1) The need for learning device training, 2) The use of innovative learning models, 3) The need for periodical clinical supervision.